GLOBALISASI DAN TANTANGAN IDENTITAS: RELEVANSI TRADISI LOKAL DALAM RESPON KEAGAMAAN - Irwan Djumat; Ermawati Ermawati (Adisam Publisher, 2025)
Globalization has a significant impact on various aspects of life, including the issue of cultural and religious identity. Global currents characterized by technological advances, communication, and transnational mobility often give rise to a homogenization of values that have the potential to erode local traditions. On the other hand, local traditions have an important role as a marker of identity as well as a social fortress in maintaining the continuity of religious values. This article aims to analyze the relevance of local traditions as a form of religious response to the challenges of globalization. The method used is qualitative with a literature study approach to examine various theoretical and empirical perspectives. The results of the study show that local traditions not only function as cultural heritage, but also as social and spiritual capital that is able to adapt, innovate, and even resist global currents. The dialectic of local and global identity creates a dynamic space for negotiation, so that traditions can be reinterpreted according to the needs of the times without losing their authenticity. Thus, strengthening local traditions is an important strategy in maintaining the sustainability of religious identity in the midst of the rapid flow of globalization.